La animación y motivación a la lectura en los tres primeros años de educación básica elemental de la unidad educativa “Indoamérica” de la parroquia Canchagua cantón Saquisilí en el año 2015. Diseño de estrategias didácticas. - Moreno Medina, Melva Lucy (2016)
The research tries to point out the animation and reading motivation among students in the first three years of Basic Education in Indoamérica Education Institution at Saquisilí town, supporting the study of the variables, in order to meet the objectives of the project, through a bibliographical research with the field research aimed at the study population to observe the incidence of animation and motivation to children bread. Concluding that students in basic education with most teachers have little knowledge of reading techniques arrive with the right knowledge through a guide to teaching strategies that strengthen animation and reading motivation and academic performance, so it is necessary to implement the proposed solution for teaching the subjects taught by teachers, strengthening the macro skills in this area such as: listening, speaking, reading and writing, creating in the student learning and meaningful intellectual enrichment , building on the student skills, interests and reading skills increase its expression and oral communication.